Comparing words, pictures and schematic faces as primes in evaluative decision task - Rebernjak, Blaž (Array, 2011)
In affective priming a presentation of positively or negatively valenced stimuli facilitates the reaction to subsequent stimuli if they are congruent in valence with the first one as compared to the situation when they are not. Numerous paradigms have been developed to measure this effect, and the question remains - do they all measure the same thing? In this study we wanted to explore how different setups of the affective priming paradigm relate to one another and to the several external criteria. The task was always that of evaluative decision – with and without the response window (EDT – Evaluative Decision Task, RWT – Response Window Technique) with words, pictures and schematic faces serving as primes resulting in six experimental situations. This was part of a pilot study with the goal of deciding which affective priming method to use in subsequent research which will try to relate individual differences in susceptibility to positive and negative primes to individual differences in personality and affectivity. Thus we used measures of positive and negative affect as external criteria for evaluation of priming approaches.